Sustaining businesses in a global turbulent environment: the role of information sharing / Sidah Idris and Suhana Mohezar - Idris, Sidah; Mohezar, Suhana (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2019)
This study aims to investigate the impact of technology capability and logistics integration commitment on information sharing as well as global supply chain competitiveness. Data were collected from 177 local manufacturing firms that are competing in global markets. The findings indicate that logistics integration commitment is significantly related with information sharing and global supply chain competitiveness. This study however, fails to establish a relationship between technology capability and global supply chain competitiveness. The findings also highlight information sharing as a mediator.